Putting people in their place: domestic space and privacy in the Amarna workmen's village - Rocha da Silva, T (2019)
This thesis contributes to the understanding of ancient Egyptian domestic space and the experience of privacy in the Workmen’s Village of Amarna during the New Kingdom (1550-1069 BCE). It provides a new framework with which to investigate domestic space, one not reduced to house units, but which integrates a large dataset from houses (artefacts, architectural features), facilities located outside the enclosure wall (pigpens, the quarry, chapels), and official buildings spatially distributed around the settlement. In addition, the use of anthropologically-orientated frameworks emphasises the relational aspect of domestic life and the way people relate to the surrounding landscape. This research approached dwellings as material culture, as a product and the medium of social relations, and not only as containers for social life. In so doing, it is possible to understand activity areas as arenas for social relations. Phenomenology is critically used and combined with a georeferencing tool (ArcGIS Pro) to understand artefact distribution within the landscape. A holistic approach to the village material offers a more complex picture of domestic space that is extended to the entire settlement. The village is then framed as a large domestic unit which conveys various experiences of privacy not limited to space, but to temporality and to status.